2013
DOI: 10.4328/jcam.1229
|View full text |Cite
|
Sign up to set email alerts
|

Occult Hepatitis B Virus Infection

Abstract: ÖzetPencere dönemi dışında Hepatit B yüzey antijeni negatif iken kan veya do-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…The incidence of OBI is different in every country, for example it has been reported between 0%-36.4% in blood donors in our country (12). According to other studies, OBI was reported actullay between 3.4% and 19% in hemodialysis patients (13).…”
Section: Discussionmentioning
confidence: 63%
“…The incidence of OBI is different in every country, for example it has been reported between 0%-36.4% in blood donors in our country (12). According to other studies, OBI was reported actullay between 3.4% and 19% in hemodialysis patients (13).…”
Section: Discussionmentioning
confidence: 63%